Dissociated vertical deviation and eye torsion: Relation to disparity-induced vertical vergence - Van Rijn, L J; Simonsz, H J; Tusscher, M P (Strabismus, 1997)
We studied the relation between vertical eye movements and binocular torsion in five subjects with dissociated vertical deviation (DVD). During trials, subject viewed a well illuminated Snellen letter chart, with both eyes uncovered during 4 seconds, Subsequently, DVD was induced by covering one eye during 4 seconds. Finally, both eyes were uncovered during 4 seconds. Several trials were recorded for each subject and covered eye. Eye movements were measured with scleral coils. We found that in all subjects, the vertical divergence followed an exponential course with a time constant of 0.67 ± 0.14 seconds on average. In three of the five subjects this vertical divergence was associated with binocular torsion (cycloversion), partly, in the form of a cycloversional nystagmus. The time course of the vertical divergence as well as the direction and nystagmic nature of the cycloversion was similar to the behaviour that was previously observed in disparity induced vertical vergence in normal subjects. In two of the subjects, the torsion that was associated with the vertical divergence was monocular. Our results indicate that DVD and disparity induced vertical vergence share the same characteristics. In addition, they demonstrate that extorsion associated with the elevation in DVD possibly but not necessarily points at a dissociated torsional deviation.